Desmosine-inspired cross-linkers for hyaluronan hydrogels - Hagel, Valentin; Wegner, Seraphine V.; Nuss, Isabell; Haraszti, Tamás; Spatz, Joachim P.; Böhm, Heike (Scientific reports, 2013)
We designed bioinspired cross-linkers based on desmosine, the cross-linker in natural elastin, to prepare hydrogels with thiolated hyaluronic acid. These short, rigid cross-linkers are based on pyridinium salts (as in desmosine) and can connect two polymer backbones. Generally, the obtained semi-synthetic hydrogels are form-stable, can withstand repeated stress, have a large linear-elastic range and show strain stiffening behavior typical for biopolymer networks. In addition, it is possible to introduce a positive charge to the core of the cross-linker without affecting the gelation efficiency, or consequently the network connectivity. However, the mechanical properties strongly depend on the charge of the cross-linker. The properties of the presented hydrogels can thus be tuned in a range important for engineering of soft tissues by controlling the cross-linking density and the charge of the cross-linker.